Análise estrutural de vigas mistas treliçadas do tipo steel-joist warren modificada - Trindade, Luiz Gustavo Cruz [UNESP]; Fernandes, Gabriela Rezende [UNESP]; Bertolino Júnior, Renato [UNESP] (FapUNIFESP (SciELO), 2017)
In this work, the failure capacity and the rupture mode of a simply supported mixed truss beam steel-joist modified warren type has been determined. The mixed steel-concrete trusses, which are very efficient to overcome large spans, are generally used in commercial and industrial buildings as well as in railway and road bridges. In many cases, in order to enable the passage of ducts, steel-joist truss beam must be considered. In this work, a span of 13.6 meters will be adopted for this truss beam for which three different analysis will be considered: i)analytical procedure ii) bi-dimensional numerical modeling by software SAP2000 [9] considering material with elastic behavior iii) three-dimensional numerical modeling considering material with elasto-plastic behavior, being the numerical analysis performed by software ANSYS [2]. For all analysis, permanent and variable actions have been considered as well as the prescriptions of the Brazilian code, being the results compared to the numerical analysis. It has been verified that for both mixed and isolated steel-joist trusses, the diagonal and amounts have presented small values for internal forces. Besides, even when regions next to the support have reached the yielding limit, the mixed action for the mixed trusses has been observed. In all the analysis the resistance load for design has been also verified, being the bigger displacements computed with the numerical modeling.
Structural analysis of mixed trusses beam steel joist modified warren type
Keywords: Mixed structure; Steel - joist; Steel structures; Trusses